2019
DOI: 10.1111/ijlh.12966
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the suitability of the World Health Organization International Reference Reagent for Hb A2 quantitation (89/666) for continued use

Abstract: Introduction The accurate determination of Hb A2 is a key marker when screening for a β‐thalassaemia carrier. Data from external quality assessment (EQA) exercises have shown a lack of alignment of Hb A2 quantitation both within and between methods. The only reference material available for Hb A2 quantitative assay at the time of writing is the World Health Organization International Reference Reagent (89/666; WHO IRR) prepared in the 1980s and not validated for all current methodologies. Method The WHO IRR wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The purpose of this study was to further investigate the suitability of the WHO IRR for HbA 2 for its continued use, a preliminary study having been undertaken by UK NEQAS in 2015 4 . In the 2015 study, participating laboratories were all based in the UK and the comparison of results from whole blood specimens to the lyophilized IRR was restricted to a single β‐thalassaemia whole blood specimen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of this study was to further investigate the suitability of the WHO IRR for HbA 2 for its continued use, a preliminary study having been undertaken by UK NEQAS in 2015 4 . In the 2015 study, participating laboratories were all based in the UK and the comparison of results from whole blood specimens to the lyophilized IRR was restricted to a single β‐thalassaemia whole blood specimen.…”
Section: Discussionmentioning
confidence: 99%
“…A study was undertaken in 2015 by UK NEQAS Haematology 4 in which an ampoule of the WHO IRR was circulated to each of 52 UK laboratories for HbA 2 estimation using their usual analytical procedures. The results indicated that the overall performance of the IRR was good and that no significant degradation had occurred in the product.…”
Section: Introductionmentioning
confidence: 99%